Generalized pustular psoriasis successfully treated with spesolimab: A case report - Noemi Brigenti; Paolo Gisondi; Francesco Bellinato; Giampiero Girolomoni (SAGE Open Medical Case Reports, 2024)
Generalized pustular psoriasis is defined as a primary, sterile, macroscopically visible pustular eruption on non-acral skin, which can occur with or without systemic inflammation and/or psoriasis vulgaris, and can either be relapsing or be persistent, according to the European Rare and Severe Psoriasis Expert Network. The treatment of generalized pustular psoriasis may be challenging. We describe a 48-year-old woman with a 15-year history of severe generalized pustular psoriasis and plaque psoriasis resistant to multiple courses of treatments with conventional and biological agents who had a rapid, complete and durable (up to 12 months) clinical remission with spesolimab, an anti-interleukin-36 receptor antagonist monoclonal antibody recently approved for the treatment of generalized pustular psoriasis flares.